Implementing Authentic Texts in Designing Reading Materials - Gulbakhor Bekmuratovna Abdukadyrova (Genius Publishing Group, 2022)
This article discusses the exposure to authentic materials (newspaper articles, online text news, magazine articles, journal articles) into EFL classroom and the benefits of the latest data that lead learners to real world communication. It is very important to students to be exposed to a real language. The real language will provide students the language that is used by the native speaker. In the end, it will meet a demand of good communication to the target language. Students will find the authentic materials useful since it can be applied in their social life and importantly improve their communication skills in the target language.
Keywords: Authentic text; reading comprehension; language skills